2019
DOI: 10.1016/j.jsv.2019.114929
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dispersion relation in anharmonic periodic mass-spring and mass-in-mass systems

Abstract: The study of wave propagation in chains of anharmonic periodic systems is of fundamental importance to understand the response of dynamical absorbers of vibrations and acoustic metamaterials working in nonlinear regime. Here, we derive an analytical nonlinear dispersion relation for periodic chains of anharmonic mass-spring and mass-in-mass systems resulting from considering the hypothesis of weak anharmonic energy and a periodic distribution function as ansatz of a general solution of the nonlinear equations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…3C). The anharmonicity of the TA phonons is demonstrated by the non-linearity in the ω(k) dispersion at low k (35)(36)(37). The second derivative of the dispersion of BiOCl (Fig.…”
mentioning
confidence: 99%
“…3C). The anharmonicity of the TA phonons is demonstrated by the non-linearity in the ω(k) dispersion at low k (35)(36)(37). The second derivative of the dispersion of BiOCl (Fig.…”
mentioning
confidence: 99%
“…Moreover, they also found that optical wave modes in nonlinear metamaterial are sensitive to parameters of the nonlinear cubic constitutive relation. Zivieri et alii [24] started from the factorization of the spatial and temporal parts of the solution and a periodic distribution function as ansatz of a general solution of the temporal part of the nonlinear equations of motion (EoM). Hence, they derived an analytical nonlinear dispersion relation for nonlinear periodic mass-spring and mass-in-mass systems.…”
Section: Background and Motivationsmentioning
confidence: 99%
“…More precisely, for a SDoF system with N = 1, the nonlinear differential equation Eq. ( 7) becomes, (24) where ceq and keq are linearization coefficients that are "equivalent" in a statistical sense [27,28,37,38]. At this stage, it is useful to introduce a state-space formulation of Eq.…”
Section: Equivalent Linearization Techniquementioning
confidence: 99%
“…Mass-in-mass (MIM) systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and nonlinear energy sinks (NESs) [19][20][21][22] are promising strategies for designing tailored metamaterials with unusual acoustical and mechanical properties. MIM lattices have been investigated for more than a decade [1][2][3], leading to stimulating concepts and applications.…”
Section: Introductionmentioning
confidence: 99%